Growth of single gold nanofilaments at the apex of conductive atomic force microscope tips. Issue 14 (5th February 2016) - Bakhti, S.; Destouches, N.; Hubert, C.; Reynaud, S.; Vocanson, F.; Ondarçuhu, T.; Epicier, T.
Abstract : Fast and one-step bias-assisted technique to grow gold filaments at the apex of commercial conductive AFM tips. Abstract : This paper describes a fast and one-step technique to grow single gold filaments at the apex of commercial conductive AFM tips. It is implemented with an atomic force microscope in air with a high relative humidity at room temperature and is based on a bias-assisted electro-reduction of gold ions directly at the tip apex. The technique requires only ad hoc substrates made of a mesoporous silica layer loaded with gold salt deposited on a conductive electrode. It leads to the growth, at the tip apex, of filaments whose length can be monitored and controlled during the growth between tens and hundreds of nanometers and whose radius of curvature can be as low as 3 nm. Made of polycrystalline gold nanostructures, the filaments are chemically and mechanically stable and conductive.